Boarding School Dalam Aktifitas Shalat (Kasus Di Mts Ma’arif Nu Kota Blitar) - Syamsul Huda (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
The widely appearance of Boarding School in Indonesia is a phenomenon worth examining. According to KarelÂ A. Steenbirk, Boarding School is a trans historical synthesis of pesantren and modernity, such that this enablesÂ the school to create an ideal educational environment in order to produce generation who believe, have goodÂ knowledge and have good works. This article is describing the result of a study examining the case of BoardingÂ School at MTs Maâ€™arif NU Kota Blitar, East Java. The writer intends to illustrate to what extent the education inÂ the Boarding School at MTs Maâ€™arif NU can foster the studentsâ€™ praying activities in order to protect themselvesÂ responding to the challenges they have currently faced. Thus, this article is intended to describe the effectivenessÂ of Boarding School in developing that praying activities.Â Data collection was conducted through observation, in-depth interview, and documentation. The obtained dataÂ were then analyzed qualitatively, by applying analysis procedures proposed by Miles and Huberman, includingÂ data reduction, data organization, data display and conclusion drawing or verification.Â The results show that: (1) in the implementation of Boarding School at MTs Maâ€™arif NU Kota Blitar, there areÂ three sorts of internal activities, morning activities, evening activities, and night activities, besides the programsÂ other than these three activities, filled with worshipping activities. Worshipping activities in the form of prayingÂ at MTs Maâ€™arif NU are obligatory for all, and must be done together, for both obligatory and suggested prayers;Â (2) The effect of the implementation of the rule that praying together is a must is that students have highÂ discipline. They are aware of their own responsibility for their need to do praying.